N-Formylated Peptide Induces Increased Expression of Both Formyl Peptide Receptor 2 (Fpr2) and Toll-Like Receptor 9 (TLR9) in Schwannoma Cells-An In Vitro Model for Early Inflammatory Profiling of Schwann Cells - Korimová, Andrea; Dubový, Petr (Cells, 2020)
Following nerve injury, disintegrated axonal mitochondria distal to the injury site release mitochondrial formylated peptides and DNA that can induce activation and inflammatory profiling of Schwann cells via formyl peptide receptor 2 (Fpr2) and toll-like receptor 9 (TLR9), respectively. We studied RT4 schwannoma cells to investigate the regulation of Fpr2 and TLR9 after stimulation with fMLF as a prototypical formylated peptide. RT4 cells were treated with fMLF at various concentrations and times with and without pretreatment with inhibitors (chloroquine for activated TLR9, PBP10 for Fpr2). Western blots of Fpr2, TLR9, p-p38, p-NFκB, and IL-6 were compared in relation to inflammatory profiling of RT4 cells and chemokine receptors (CCR2, CXCR4) as potential co-receptors of Fpr2. fMLF stimulation upregulated Fpr2 in RT4 cells at low concentrations (10 nM and 100 nM) but higher concentrations were required (10 µM and 50 µM) when the cells were pretreated with an activated TLR9 inhibitor. Moreover, the higher concentrations of fMLF could modulate TLR9 and inflammatory markers. Upregulation of Fpr2 triggered by 10 nM and 100 nM fMLF coincided with higher levels of chemokine receptors (CCR2, CXCR4) and PKCβ. Treating RT4 cells with fMLF, as an in vitro model of Schwann cells, uncovered Schwann cells' complex responses to molecular patterns of release from injured axonal mitochondria.
Keywords: toll-like receptor 9; Inflammation; Up-Regulation; neurilemom; Cell Line, Tumor; chlorochin; receptory CXCR4; Receptors, Formyl Peptide; N-formylmethionin-leucyl-fenylalanin; signální transdukce; N-Formylmethionine Leucyl-Phenylalanine; upregulace; Schwannovy buňky; Signal Transduction; Receptors, CXCR4; Toll-Like Receptor 9; zánět; krysa rodu Rattus; Receptors, CCR2; Neurilemmoma; Animals; Chloroquine; zvířata; Rats; Schwann Cells; receptory pro formylované peptidy; nádorové buněčné linie; receptory CCR2